Longitudinal dynamics and health impact of Hepatozoon procyonis (Apicomplexa: Hepatozoidae) on naturally infected ring-tailed coatis Nasua nasua (Carnivora: Procyonidae) from Midwestern Brazil - Perles, L. [UNESP]; Macedo, G. C. de; Barreto, W. T.G.; Francisco, G. V. [UNESP]; Herrera, H. M.; Barros-Battesti, D. M. [UNESP]; Machado, R. Z. [UNESP]; André, M. R. [UNESP] (Elsevier, 2022)
This study aimed to morphologically and molecularly detect Hepatozoon procyonis in ring-tailed coatis’ (Nasua nasua) blood and associated ticks from central-western Brazil, Campo Grande, Mato Grosso do Sul state and also evaluate the impact of the protozoa in blood parameters and coati´s health. Samplings were performed in a conservation area Parque Estadual do Prosa (PEP) and in a Brazilian Air Force Private Area namely Vila da Base Aérea (VBA), between March 2018 and April 2019. We collected 165 blood samples, 61 from recaptured coatis. Peripheral blood smears were stained with Romanovsky-type stain for H. procyonis parasitemia assessment. DNA extracted from blood samples and ticks (Amblyomma spp.) were submitted to a nested PCR (nPCR) assay based on the 18S rRNA gene for Hepatozoon spp. Out of 104 individuals sampled, 80 (77%) were positive for H. procyonis in at least one capture. Overall, 67/165 (40.6%) blood smears showed H. procyonis gametocytes (PEP: 41/63 - 65%; VBA: 26/102 - 25.5%). Parasitemia based on 500 assessed leucocytes ranged from 1 (0.2%) to 50 (10%) and 1 (0.2%) to 25 (5%), from animals sampled in PEP and VBA, respectively. Fluctuation on the parasitemia was observed during recaptures. nPCR results showed higher positivity when compared to blood smears, i.e. 112/165 (68%) positive blood samples [PEP: 41/63 (65%), VBA: 26/102 (25.5%)]. In total, 63/248 (25.4%) tick DNA samples were positive at nPCR for Hepatozoon sp., including 32/87 (37%) pools (1 to 10 larvae) of Amblyomma larvae, 21/105 (20%) pools (1 to 5 nymphs) of Amblyomma sculptum nymphs, 9/43 (21%) pools (1 to 5 nymphs) of Amblyomma dubitatumnymphs, and 1/12 (8%) A. sculptum adult female. The partial 18S rRNA sequence from one coati's blood sample and one representative of each positive tick species randomly selected from each area for sequencing (1,000 bp) showed 100% identity with sequences of H. procyonis from GenBank previously detected in coatis. Regarding H. procyonis infection, no statistical differences were obtained when comparing males vs. females (p-value 0.67), immature animals vs. adults (p-value 0.31), rainy vs. dry season (p-value 0.51) and sampling location (p-value 0.42). No noticeable alteration in blood parameters or heath status was observed in parasite animals. H. procyonis circulates in a high prevalence in coatis from central-western Brazil. Parasitemia fluctuates among different coatis’ recaptures and apparently the infection has no influence in coatis’ hematological and clinical parameters.
Keywords: 18S rRNA; Hepatozoonosis; Parasitemia; Procyonids; Wildlife conservation